Natural Infection with Cryptosporidium galli in Canaries (Serinus canaria), in a Cockatiel (Nymphicus hollandicus), and in Lesser Seed-Finches (Oryzoborus angolensis) from Brazil - Antunes, Romulo G. [UNESP]; Simoes, Daniel C. [UNESP]; Nakamura, Alex A. [UNESP]; Meireles, Marcelo Vasconcelos [UNESP] (Amer Assoc Avian Pathologists, 2008)
Proventricular infection by Cryptosporidium sp. or Cryptosporidium galli has been associated with mortality, weight loss, diarrhea, and pasty feces. The purpose of this study is to report the occurrence of natural C. galli infection in canaries (Serinus canaria), in a cockatiel (Nymphicus hollandicus), and in lesser seed-finches (Oryzoborus angolensis) with clinical complaints of apathy and sporadic mortality. Screening for Cryptosporidium spp. using microscopic examination of fecal samples and stained smears, histopathology, and nested polymerase chain reaction for actin gene and 18S ribosomal RNA gene following sequencing of amplified fragments allowed for the identification of C. galli. To the best of our knowledge, this is the first report of C. galli in birds in Brazil and the first report of this species in lesser seed-finches.
Keywords: Cryptosporidium galli; natural infection; canary; lesser seed-finch; cockatiel; Brazil